The effect of curing hepatitis C with direct-acting antiviral treatment on endothelial function. Issue 8 (November 2018) - Davis, Joshua S; Young, Melissa; Lennox, Sandra; Jones, Tracey; Piera, Kim; Pickles, Robert; Oakley, Stephen
Background: Epidemiological data suggest that chronic HCV infection (CHC) is associated with increased cardiovascular risk, but it is unknown if it is associated with endothelial dysfunction. We aimed to assess the effect of antiviral treatment on endothelial function in non-cirrhotic adults with CHC. Methods: Self-controlled before and after study. All patients had genotype-1 CHC and were treated with 12 weeks of paritaprevir/ritonavir, ombitasvir and dasabuvir (PrOD), with ribavirin added for those with geno-type-1a infection. Endothelial function was assessed at three time points before antiviral treatment, at treatment weeks 1, 4, 8 and 12, and 12 weeks after the end of treatment. The main assessment tools were reactive hyperaemia peripheral arterial tonometry (RHPAT) and serum concentrations of angiopoietin-2 (Ang-2) and E-selectin. Results: A total of 16 patients were enrolled. Mean (sd ) age was 51.4 (6.9) years and 11 participants (69%) were male. All 16 patients achieved a sustained virological response. The mean (sd ) baseline RHPAT index was 2.05 (0.48), and there was no significant change during treatment (mean within-patient change from baseline to end of treatment =-0.23 [0.45]; P = not significant). There was a significant improvement in both mean Ang-2 (baseline 2.44 [0.79] ng/ml, within-patient change -0.60 [0.44]; P <0.001) and E-selectin (baseline 48.7 [21.5] ng/ml, within-patient change -14.4 [13.0]; P <0.001). Conclusions: Removing HCV viraemia is associated with a significant improvement in endothelial function as measured by serum markers, but not in bedside micro-vascular reactivity. Chronic HCV viraemia may be associated with endothelial cell dysfunction and therefore long-term cardiovascular risk.